1984
DOI: 10.1152/ajpgi.1984.246.6.g725
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary iron in maturation of rat small intestine at weaning

Abstract: The weanling process is characterized by the transition from a liquid diet poor in iron (rat milk) to a solid diet high in iron (chow pellets). To examine the effects of iron content of the weanling diet on terminal maturation of rat small intestine, suckling pups, nursed by iron-sufficient mothers, were weaned by day 16 onto a solid basal diet that was either deficient [low-iron diet (LID): 0.5 mg iron/100 g solid] or high [high-iron diet (HID) controls: 30 mg iron/100 g solid] in iron. The animals were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…In agreement with previous studies, it was observed that iron-deficient Wistar rats have significantly lower sucrase and lactase activities compared with their control littermates (2,4,5,9,16,20,31,38). This decreased activity cannot be attributable to changes in kinetic properties of the enzymes as evidenced by no significant differences in K m values, inferring that it is primarily due to reduced quantities of the enzyme present in the mucosa.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with previous studies, it was observed that iron-deficient Wistar rats have significantly lower sucrase and lactase activities compared with their control littermates (2,4,5,9,16,20,31,38). This decreased activity cannot be attributable to changes in kinetic properties of the enzymes as evidenced by no significant differences in K m values, inferring that it is primarily due to reduced quantities of the enzyme present in the mucosa.…”
Section: Discussionsupporting
confidence: 90%
“…One unit was defined as the ability to generate 1 mol glucose/min, and results expressed as units per gram of wet mucosa mass. Wet mucosa mass was used to calculate specific activity rather than protein content, as protein concentration in the mucosa does not significantly change during iron deficiency (4,5).…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations